The influence of self-pollen deposition on female reproductive success in a self-incompatible plant, Akebia quinata - Wang, Chun-Hui; Zou, Ting-Ting; Liu, Wei-Qi; Wang, Xiao-Fan (Frontiers in Plant Science, 2022)
Geitonogamy is inevitable in hermaphrodite and monoecious. Even for self-incompatible species, the negative effects of self-pollen are unavoidable when geitonogamous or self-mating occurs. However, the influence of self-pollen on consecutive development of flowers (e.g., fruiting and seeding) was seldom evaluated. Here, the self-incompatible monoecious species, Akebia quinata, was used to estimate the influence of self-pollen deposition. We evaluated the extent of pollen limitation and geitonogamous mating under natural conditions by count of stigmatic pollen load and pollen tracking experiment. Hand pollination with different amount and combinations of self vs. cross pollen grains was applied to detect the response of fruit and seed set. The results showed that geitonogamy and pollen limitation occurred under natural conditions in A. quinata. Carpel numbers, ratio of self- and cross-pollen, and the interactive effect of ratio of self- and cross-pollen and total mixed pollen numbers, and not total pollen grain number, determined the effect of self-pollen on female reproductive success. The effect of self-pollen depended on its intensity. In general, the transfer of self-pollen significantly affected young fruit set. However, a little self-pollen together with cross-pollen did not reduce young fruit production. Although self-incompatible plants have evolved physiological mechanisms that reduce self-fertilization, our results provide new insights into the effects of self-pollen and the adaptive significance of self-incompatible monoecious species.